Perancangan dan Pembuatan Media Pembelajaran Mata Kuliah Kinematika dan Dinamika - Muhammad Arsyad (Jurnal Teknik Mesin Sinergi, 2009)
The objectives of this research is design and make of studying media for Cinematic and Dynamic subject which student should be interesting to follow studying in order to simple understanding of material the subject, student could be more activies and enjoy in teching process, to increase performance and profesionalism of teacher, and finally score of student could be more fine. For catch those goals, the activities divided by two step: (1) The making material of teaching for a semester, (2) Implementation of material teaching in the class for a semester. The product of teaching grant project is Course note, Material of Teaching, and Prototype of material teaching. Developing methode of studying sistem which applicated on this project is speech, group discuss, and evaluation. But Application strategy which applicated is applicative assignment, Dialog, making of course note, and teaching by multimedia system. Result of testing shown that motivation, attention, and interesting of student should be better than before them, the student is more active to fill this subject, lecturer could be profetional to teach, and the average score of student could be more. This is method could be to develop for internet basic system.